14. EARLY OUTCOMES OF VENTRICULAR SEPTAL DEFECT REPAIR VIA MINIMALLY INVASIVE APPROACH AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness and safety of minimally invasive surgical repair of ventricular septal defect (VSD) via the right mid-axillary approach at Nghe An Obstetrics and Pediatrics Hospital.Subjects and Methods: From January 2023 to October 2024, 38 patients diagnosed with VSD underwent minimally invasive surgical repair via the right mid-axillary approach at Nghe An Obstetrics and Pediatrics Hospital in a retrospective study.Results:Among the 38 patients undergoing minimally invasive VSD repair, 18 were male and 20 were female. The average weight and age of the patients were 11.45 ± 1.36 kg and 33.45 ± 7.36 months, respectively. The average defect size was 7.14 ± 0.51 mm. Additionally, 14 patients (36.8%) had a patent ductus arteriosus (PDA). Defect locations were classified as follows: 27 patients (71.1%) had perimembranous VSD, 9 patients (23.68%) had subaortic VSD, and 2 patients (5.22%) had doubly committed subarterial VSD. The average surgery duration was 219.1 ± 7.56 minutes, with an average aortic clamping time of 70.5 ± 4.44 minutes and a cardiopulmonary bypass time of 106.6 ± 5.05 minutes. The average skin incision length was 5.03 ± 0.17 cm, and the mean ventilation time was 24.81 ± 2.67 hours. No mortality or conversion to another surgical approach was reported. Three patients (7.89%) exhibited minor residual shunting immediately after surgery. Follow-up examinations revealed no residual shunting and no post-operative thoracic deformities.Conclusion: Early results of minimally invasive VSD repair in children at Nghe An Obstetrics and Pediatrics Hospital are safe and feasible. Further studies with larger patient populations and longer follow-up periods are needed to accurately assess the effectiveness of this treatment approach.
Keywords: Ventricular septal defect; minimally invasive surgery